Effects of niobium-loading on sulfur dioxide gas-sensing characteristics of hydrothermally prepared tungsten oxide thick film - Viruntachar Kruefu (2018)
© 2015 Viruntachar Kruefu et al. Nb-loaded hexagonal WO3nanorods with 0-1.0 wt% loading levels were successfully synthesized by a simple hydrothermal and impregnation process and characterized for SO2sensing. Nb-loaded WO3sensing films were produced by spin coating on alumina substrate with interdigitated gold electrodes and annealed at 450°C for 3 h in air. Structural characterization by X-ray diffraction, high-resolution transmission electron microscopy, and Brunauer-Emmett-Teller analysis showed that spherical, oval, and rod-like Nb nanoparticles with 5-15 nm mean diameter were uniformly dispersed on hexagonal WO3nanorods with 50-250 nm diameter and 100 nm-5 μm length. It was found that the optimal Nb loading level of 0.5 wt% provides substantial enhancement of SO2response but the response became deteriorated at lower and higher loading levels. The 0.50 wt% Nb-loaded WO3nanorod sensing film exhibits the best SO2sensing performances with a high sensor response of 10 and a short response time of 6 seconds to 500 ppm of SO2at a relatively low optimal operating temperature of 250°C. Therefore, Nb loading is an effective mean to improve the SO2gas-sensing performances of hydrothermally prepared WO3nanorods.